Timing and Time Perception: Procedures, Measures, & Applications - Vatakis, Argiro; Balcı, Fuat; Di Luca, Massimiliano; Correa, Ángel (Brill, 2018)
Timing and Time Perception: Procedures, Measures, and Applications is a one-of-a-kind, collective effort to present -theoretically and practically- the most utilized and known methods on timing and time perception. Readership: All interested in the methods utilized in measuring timing and time perception with particular emphasis on graduate and postgraduate students, educators, and researchers.